Friction Stir Welding and Processing VII 2013
DOI: 10.1002/9781118658345.ch14
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heat Input on Friction Stir Welding for the ODS Steel MA956

Abstract: The oxide dispersion strengthened steel MA956 was friction stir welded using eight different rotational speed/translational speed combinations using a polycrystalline cubic boron nitride tool. Weld parameter conditions with high thermal input produced defect-free, full penetration welds. Electron backscatter diffraction showed a significant increase in grain size in the stir zone, a body centered cubic torsional texture in the stir zone, and a sharp transition in grain size across the thermo-mechanically affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 17 publications
2
11
0
Order By: Relevance
“…Additional work has conclusively shown that FSW causes significant oxide particle coarsening which reduces the strengthening contribution of the dispersed oxides considerably [22]. The research presented herein combined with related reports on the evolved microstructure [21] and oxide particle morphology [22] aims to establish the processing, microstructure, and material property relationships of the ODS alloy MA956 following FSW with a variety of welding conditions. When combined the results show that MA956 can be manufactured and joined in a manner that maintains sufficient high temperature strength for use in nuclear applications.…”
Section: Introductionmentioning
confidence: 82%
See 4 more Smart Citations
“…Additional work has conclusively shown that FSW causes significant oxide particle coarsening which reduces the strengthening contribution of the dispersed oxides considerably [22]. The research presented herein combined with related reports on the evolved microstructure [21] and oxide particle morphology [22] aims to establish the processing, microstructure, and material property relationships of the ODS alloy MA956 following FSW with a variety of welding conditions. When combined the results show that MA956 can be manufactured and joined in a manner that maintains sufficient high temperature strength for use in nuclear applications.…”
Section: Introductionmentioning
confidence: 82%
“…Plunge force was maintained constant at 17.8 kN (4000 lbf). For the current paper, only fully consolidated welds were analyzed although previous research on processing and microstructure relationships included defective welds [21]. The three defect free FSW parameter conditions analyzed in this paper are (1) 400 RPM/100 MMPM (the lowest heat input condition), (2) 300 RPM/50 MMPM (slightly higher heat condition), and (3) 500 RPM/25 MMPM (the highest heat input condition).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations